PTH-005 Peg insertion: endoscopist's recognition of patient comfort and recall. (22nd June 2015) - Axe, K; Etezadi, A; Mapstone, M; Jones, F; Galliford, S; Pinch, N; Hawthorne, AB
Abstract : Introduction: Endoscopy tolerance is improved in patients with higher sedation scores; 1 however, endoscopists underestimate procedure related pain 2 and consider it unlikely to be remembered by patients. 3 We compared the medication dose and endoscopist's assessment of pre-procedure anxiety, sedation score, patients' pain and anticipated procedure recall with a post-procedure patient comfort questionnaire. Method: Endoscopist's assessment of patient comfort and recall were recorded at the time of procedure, patient survey was completed by a specialist nutrition team the day after the PEG. Results: 67 procedures were included; 56 endoscopist assessments and 51 nutrition team visits, of these 20 patients were excluded due to communication issues. Midazolam was used in all procedures, average 2.0–3.0 mg, Fentanyl was used in 5 procedures, 63/67 were judged as drowsy or lightly asleep, 4 were felt to be awake. 39/49 procedures took <15 mins, longer procedures were judged more difficult by endoscopist's. Patients didn't report increased discomfort with longer procedures. Average patient pain score was 5/10. Endoscopist's felt that drowsier patients were more comfortable; however, 65% patients reported moderate or severe discomfort independent of drowsiness level. Patients judged to have no or mild pain by endoscopists reported moderate or severe pain in 14/23 cases (61%). Endoscopists felt that 37/50 patients wouldn't recall the procedure; patients seeming to be more uncomfortable were judged more likely to recall the procedure. Patients giving higher discomfort scores were more likely to recall the procedure; however, endoscopists judged 25% patients (4/16) who recalled the procedure as unlikely to do so. Conclusion: Endoscopists were poor at assessing patient discomfort, patient discomfort increased with increased awareness and lower Midazolam dose. Increasing the use of sedation and adding Opiod analgesia during PEG may help improve patient comfort and reduce recall post procedure. Disclosure of interest: None Declared. References: Abraham N, Barkun A, Larocque M, Fallone C, Mayrand S, Baffis V, Cohen A, Daly D, Daoud H, Joseph L. Predicting which patients can undergo upper endoscopy comfortably without conscious sedation. Gastrointest Endosc. 2002;56(2):180–9 Thanvi BR, Munshi SK, Vijayakumar N, Taub N, Lo TC. Acceptability of oesophagogastroduodenoscopy without intravenous sedation: patients' versus endoscopist's perception with special reference to older patients. Postgrad Med J. 2003;79(937):650–1 Von Delius S, Hollweck R, Schmid RM, Frimberger E. Midazolam-pain, but one cannot remember it: a survey among southern German endoscopists. Eur J Gastroenterol Hepatol. 2007;19(6):475–70